(untitled) (Itinera, 2012)
Gioacchino Di Marzo (1839-1916) was a extraordinarily productive polygrapher. His work represents the very first attempt to bring to Sicily an approach to the History of Art methodologically and scientifically grounded. Starting from the early Delle Belle Arti in Sicilia, Di Marzo declares his adhesion to the Post-Hegelian milieu, although highly contaminated with the still vital heritage of Eighteenth Century culture (Batteux, Winckelmann, Arteaga, etc.). This essay is the first accurate reading according to a aesthetological perspective of the Introduction to the text, as it highlights the essentially ambivalent position of the scholar between modernity and tradition.